Exploring Behavioral Intention Toward Sustainable Ecotourism Development among Local Residents Working in the Mekong Delta, Vietnam - Huynh Truong Huy; Ho Le Thu Trang (Geographica Pannonica, 2026)
This study aimed to explore various levels of local residents’ behavioral intention toward sustainable ecotourism development in the Mekong Delta, Vietnam and identified their key determinants. Using convenience sampling method, a total of 302 responses were used for data analysis. The proposed model involving three dimensions of residents’ perceptions (economic, sociocultural and environmental sustainability) and attitude was developed to determine the formation of local residents’ participation intention. Furthermore, residents’ intention in sustainable development of ecotourism was examined through a second-factor latent variable with four aspects including sustainable community development, natural resources conservation, cultural tradition preservation, and participation in planning and managing ecotourism development. The findings demonstrated that residents’ perceptions had direct impacts on their participation intention, which were partially mediated by their attitude. Notably, perceived environmental benefits of local people had the strongest overall effect among the variables examined. Finally, theoretical and managerial implications are discussed.